HEAT LOSS OF A BRICK BUILDING WALL DEPENDING ON THE THICKNESS OF THERMAL INSULATION MATERIAL - Bluks, Oskars; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The proposed study has been completed to calculate and compare heat losses through the building wall depending on the thickness of the thermal insulation material layer. The aim of the work is to find the optimal thickness of thermal insulation material. The study concludes that heat loss is directly dependent on the thickness of the thermal insulation layer, but the greatest effect is achieved with the first layer.